2005
DOI: 10.4049/jimmunol.174.12.8072
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Adhesion to Xenogeneic Endothelium during Laminar Flow Is Dependent on α-Gal-Mediated Monocyte Activation

Abstract: Monocytes are the predominant inflammatory cell recruited to xenografts and participate in delayed xenograft rejection. In contrast to allogeneic leukocytes that require up-regulation of endothelial adhesion molecules to adhere and emigrate into effector tissues, we demonstrate that human monocytes adhere rapidly to unstimulated xenogeneic endothelial cells. The major xenoantigen galactoseα(1,3)galactoseβ(1,4)GlcNAc-R (α-gal) is abundantly expressed on xenogeneic endothelium. We have identified a putative rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…In the previous study, we found that the fluorescent signal after incubation of polymeric ␣-gal and human monocytes was significantly decreased in the absence of Ca 2ϩ /Mg 2ϩ . This led us to the assumption of the involvement of C-type lectins (15). Conversely, we demonstrated in the current study that the binding of Galectin-3 to its ligand is calcium independent.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…In the previous study, we found that the fluorescent signal after incubation of polymeric ␣-gal and human monocytes was significantly decreased in the absence of Ca 2ϩ /Mg 2ϩ . This led us to the assumption of the involvement of C-type lectins (15). Conversely, we demonstrated in the current study that the binding of Galectin-3 to its ligand is calcium independent.…”
Section: Discussionmentioning
confidence: 68%
“…Indeed, we have previously demonstrated specific and saturable binding of a soluble Gal-␣(1,3)Gal-␤(1,4)GlcNAc-R fluorescent probe to monocytes in suspension (15). Interestingly, monocytes obtained from different donors showed a variation in MFI, while there was essentially no binding to lymphocytes ( Fig.…”
Section: ␣-Gal Is a Ligand For Human Monocyte Lectinsmentioning
confidence: 99%
See 3 more Smart Citations